Women's empowerment in agriculture index (WEAI): incorporating gender and mixed methods into nutrition research - Malapit, Hazel J.; Martinez, Elena M. (International Food Policy Research Institute, 2017)
Presented by Hazel Malapit and Elena Martinez (IFPRI), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017